POLITENESS STRATEGIES REFLECTED BY THE MAIN CHARACTER IN “BRIDGE TO TERABITHIA” MOVIE - Hidayatul Fitria; Dian Riesti Ningrum; Suhandoko Suhandoko (Department of Master of Linguistic, Universitas Airlangga, 2020)
This research aims to identify politeness strategies reflected by the main character in “Bridge to Terabithia” movie. Qualitative method is used by the researcher to analyze the data. The data are the utterances of the main character that include politeness strategies. In analyzing the data, the researcher uses theory by Brown and Levinson (1987) about politeness strategies. The results of this research show that there are four types of politeness strategies which used by the main character in this movie. The most type that used is bald on record strategy and positive politeness strategy. The factors in using politeness strategies by the main character in this movie are payoffs in each strategy and circumstances (sociological variables). The researcher hopes that this research could give the contribution toward the next researchers. Moreover, some recommendations are given to the next researchers who will do the same research on politeness strategies either in the movie or in other forms. Key Words: Politeness strategies, Bridge to Terabithia